The practice and potential of the SITES v2 rating system for the sustainable design of a landscape: A case study of Chicago’s Navy Pier - Jin, Lin; Wang, Yilei (Frontiers in Environmental Science, 2023)
The landscape is a synthesis of the cultural and natural processes of a place, which can be designed and maintained to be ecologically resilient and thus to be able to both improve and regenerate the natural benefits and services of ecosystems. As such, how to develop and manage our landscape will play a significant role in the health and welfare of humans in the future. The Sustainable Sites Initiative was an interdisciplinary group effort that developed a rating system that identifies and advances best practices for landscape architecture. SITES v2 Rating System was produced through a multi-year iterative process. It is presented as a systematic, comprehensive set of guidelines to incentives sustainable landscape practices by using an ecosystem services framework. Opportunities for continuing research on how SITES v2 encourages the creation of a landscape sustainability system and drive more sustainable land development to become apparent as it expands in application, scope, and impact. In this study, taking the SITES gold-certified project Navy Pier in Chicago as a case study, the authors aim to illustrate the practice and potential of SITES v2 for sustainable design of a landscape. The results show as an important tool for transformation from theory to the implementation of ecosystem services, SITES v2 is being used to guide design decisions toward sustainable outcomes. It also can promote the entire project accountable to a higher standard of best practices and result in a more sustainable site. In the context of practices of contemporary landscape architecture, SITES v2 may lead to the transformation in sustainable landscape design. Our study can promote the ongoing application of SITES v2 and the creation of a better sustainable landscape through design. It holds the potential to highlight how the methodology on which SITES has been created, can be linked with future cities development and urban landscape management.